Digitalization and Cyber Risks - V. G. Khalin; G. V. Chernova (Управленческое консультирование)
Digitalization, considered in a broad sense as the most important modern trend of social development, is generally accompanied not only by positive consequences for the economy and society, but also by challenges, threats, as well as negative consequences of the implementation of these threats. Digitalization, considered in a narrow sense as the transformation of information of any kind into its digital form and involving the use of digital information, can also be described by challenges, threats, negative consequences and risks. Among the latter, a significant role is played by the risks of violating the security of digital information — cyber risks. Since they can have a negative impact on digitalization, considered both in a broad and narrow sense, there is a problem of allocating cyber risks and managing them in order to reduce possible losses and damage caused by the implementation of these cyber risks. The article defines the interrelationships of the concepts of digitalization, challenge, threat, negative consequence and risk; identifies the role and justifies the high importance of a cyber call as a requirement to ensure the security of digital information; determines the factors of influence on cyber risks; suggests a variant of building a cyber risk management program, the implementation of which will contribute to reducing the possible negative consequences of digitalization caused by a violation of the security of digital information.